English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

ln(5-4x)=-3
e^(-3) = 5 - 4x
4x = 5 - e^(-3)
x = 5/4 - e^(-3)/4
x = 5/4 - 1/(4e^3)

e^(4x+3)-9=0
e^(4x+3) = 9
4x + 3 = ln(9)
4x = ln(9) - 3
x = [ln(9) - 3]/4

2006-11-13 11:33:55 · answer #1 · answered by Anonymous · 0 0

ln(5 - 4x) = -3
5 - 4x = e^(-3)
5 - 4x = 1/(e^3)
-4x = (1/(e^3)) - 5
-4x = (1 - 5e^3/(e^3)
x = -(1 - 5e^3)/(4e^3)

ANS : x = (5e^3 - 1)/(4e^3) or (5/4) - 4e^(-3)

2006-11-13 22:02:59 · answer #2 · answered by Sherman81 6 · 0 0

First question: x = 1.2375532

Second question: x = -.200069

2006-11-13 19:38:41 · answer #3 · answered by cevfuture 1 · 0 1

fedest.com, questions and answers